دور الاتصال في زيادة فعالية أداء الموارد البشرية دراسة ميدانية بمؤسسة سونلغاز بالمسيلة - غنية, دعدع (كلية العلوم الانسانية و الاجتماعية - جامعة محمد بوضياف المسيلة, 2013)
هدفت الرسالة إلى معرفة دور الاتصال في زيادة فعالية أداء الموارد البشرية في مؤسسة صيانة التجهيزات الصناعية(سونلغاز ) ،وقد استخدمنا المنهج الوصفي التحليلي حيث تم توزيع 100 استمارة على المبحوثين ، وتم اختيار العينة بطريقة عشوائية بسيطة ، واستمدت الدراسة أهميتها من الاهتمام المتزايد بالاتصال وتقنياته ودوره في تحسين فعالية الأداء، إضافة إلى أن كثيرا من الناس يجهلون أثر الاتصال على أداء الموارد البشرية في المؤسسة الاقتصادية، وأهميته في بناء التفاعلات بين أفراد مجتمع العمال داخل بمختلف أشكاله ووسائله والتعرف على دوره من خلال الواقع، وذلك من الدراسة الميدانية، حيث يعتبر الاتصال الوسيلة الفعالة والمحققة لأهداف تلك المنظمات فنشاط المنظمات الإدارية المتمثل فيما تقوم به من تخطيط، وتنظيم، وتوجيه، ورقابة، واتخاذ قرارات قائم أساسا على نظم الاتصالات التي يمكن من خلالها تمرير الأوامر والتعليمات والتوجيهات من الإدارة العليا إلى الإدارات الفرعية وبالتالي المرؤوسين والقائمين بتنفيذ الأوامر، وهكذا تكمن الاتصال ودوره في المنظمات ويمكن إبراز أهمية الدراسة الحالية من ناحيتين علمية وأخرى عملية. وتتمثل أهمية الدراسة من الناحية العلمية في إثراء المعرفة العلمية في مجال الاتصال ووسائله وتقنياته الموارد البشرية في المؤسسة الاقتصادية.أما من الناحية العملية فتتمثل في استفادة المسؤولين بالقيادات العليا والوسطى في المؤسسة الاقتصادية من نتائج الدراسة وما تقدمه لهم من بيانات صادقة وموثوقة مستمدة من الدراسات الميدانية، حيث تمكنهم من تفعيل الاتصالات والاستفادة من تقنياته من أجل الوصول إلى أداء متميز وفعال بأسلوب علمي وموضوعي.وقد أظهرت النتائج ما يلي : على الرغم من أن المؤسسة مستقلة وفي ظل ما تمليه عليها مبادئ استقلالية المؤسسات التي تهدف إلى تفعيل العوامل التنظيمية المختلفة بهدف تفعيل أداء العمال وبالتالي تفعيل إنتاجية المؤسسة في خضم المنافسة واقتصاد السوق، العوامل التنظيمية ومؤشرات الأداء فعالة في المؤسسة مجال الدراسة ترتبت عنها مؤشرات ايجابية لأداء العمال الدائمين في خضم نقص معدلات التغيب ودوران العمل، ومحاولة التأقلم والتحكم في التكنولوجيا المستخدمة، كما أنها تسعى جاهدة للتأقلم مع التكنولوجيا الحديثة إلا أنها تفتقرإلى عدم الانضباط الذاتي والتي برزت على شكل تصرفات تضر بالمؤسسة كاللامبالاة والتهاون وتحجج العمال الدائمين بحجج مختلفة للتهرب من إنجاز أعمالهم كالتحجج بقضاء الحاجة، وتأدية الصلاة...وغيرها من المظاهر السلبية التي تحد من فعالية الأداء باستمرار. إلا أن هذه المؤشرات السلبية لا تظهر عند العمال المؤقتين، في خضم العوامل التنظيمية السابقة، ففاعلية الأداء بالنسبة لهذه الفئة من العمال تحددها عوامل أخرى جسدتها الدراسة الإمبريقية، الإكراه والقهر في خضم العلاقة التعاقدية التي تربط العامل بالمؤسسة والتي تجبره على العمل تخوفا من فقدان منصب عمله في ظل الظروف الاقتصادية والاجتماعية التي من الصعب الحصول على وظيفة أخرى. Summary of the Study Aimed message to know the role of communication in the more effective functioning of human resources in the enterprise maintenance of industrial plants (Sonelgaz), we have used the descriptive analytical method has been distribute 100 form on the respondents, was chosen as the sample randomly simple, derived study importance of the growing interest in contacting techniques and role improving the effectiveness of performance, in addition to that many people are unaware of the impact of communication on the performance of human resources in the enterprise economic, and its importance in building interactions between members of the community workers in various forms and methods and to identify the role of the fact, and that of the field study, where the contact means effective and achieved the objectives of those organizations فنشاط administrative organizations represented in its planning, organizing, directing, and controlling, and make decisions based primarily on communications systems in which they can pass orders and instructions and directives from senior management to departmental sub and thus subordinates and implementers commands, and so is communication and its role in organizations and can highlight the importance of the current study in two ways and other scientific process. The importance of the study of the scientific to the enrichment of scientific knowledge in the field of communication, methods and techniques of human resources in the enterprise economy. In practice is to take advantage officials Leadership upper and middle in the organization of economic results of the study and what they offer their data honest and reliable derived from field studies, where they can activate communications and take advantage of the techniques in order to reach high performance and effective scientific manner and objective. Results showed the following: Although the company independent and under the dictates of the principles of institutional autonomy, which aims at activating the organizational factors with the aim of activating the performance of workers and thus activating the productive enterprise in the midst of competition and the market economy, organizational factors and performance indicators effective in the enterprise area of study resulting from them are positive indications for the performance of permanent workers in the midst of lack of absenteeism and turnover work, and try to adapt and control technology used, as it strives to adapt to modern technology but it lack of self-discipline, which emerged in the form of actions harm Head complacency he contended permanent workers under various pretexts to evade the completion of their spending need, and praying ... and other negative phenomena which limit the effectiveness of performance consistently. However, these negative indicators do not appear when temporary workers, in the midst of organizational factors previous performance for this category of workers identified other factors embodied study empirical, coercion and oppression in the midst of the contractual relationship between worker organization, which force him to work for fear of losing office work Under the economic and social conditions that are difficult to get another job.
Keywords: الاتصال -تقنيات الاتصال- أداء الموارد البشرية